(untitled) (Applied Biological Research, 2016)
Field experiments were conducted in 2013 and 2014 with the aim to develop optimal nitrogen management for Basmati rice cv. ‘Pusa Sugandh-3’ using leaf colour chart (LCC). The treatments included no nitrogen (N0) treatment, three fixed time (60, 90 and 120 kg N ha-1) and four real time nitrogen management treatments. Grain and straw yield, total N uptake and various indices of N use efficiency were measured in both the years. The best response in all the parameters assessed was achieved with LCC treatments maintained at 20 kg N ha-1 (LCC 420) and 30 kg N ha-1 (LCC 430) . However, LCC 420 treatment had significantly higher nitrogen use efficiency (NUE) as compared to LCC 430 treatment because the nitrogen applied in former treatment was 20 kg ha-1 lesser than the later, while as yield in both the treatments was same. Based on the principle that threshold value is the one which simultaneously optimizes grain yield and NUE, LCC 420 treatment was adjudged as threshold value for real time N management in Basmati rice variety ‘Pusa Sugandh-3’ under temperate conditions of Kashmir.